Trade and decent work: Adequate earnings in the Mexican manufacturing industries - Benjamín Alemán Castilla (International Labour Organization (ILO), 2021)
This paper analyses the impact of non-preferential trade liberalization and exposure to globalization on "adequate earnings" in the Mexican manufacturing industries between 2003 and 2020, using data from the National Survey of Occupation and Employment and from the annual surveys of manufacturing industries. By means of panel data and three-stage least squares estimation strategies, it is found that, although exposure to globalization is not robustly associated with gross daily wages per employee, non-discriminatory trade liberalization and exposure to globalization contributed to a reduction in both the working poverty rate among employed persons and the share of employees with low pay rates. The paper is a contribution to the project 'Trade, enterprises and labour markets: Diagnostic and firm level assessment (ASSESS)', jointly funded by the European Commission and the ILO.
Keywords: 330